PENGARUH TEPUNG BUAH NIPAH TERHADAP KARAKTERISTIK BISKUIT TINGGI SERAT - Ulyarti; Surhaini; Adha Farwati (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2021)
The amount of fibre consumption in Indonesia is lower than recommended by WHO. The use of nypa flour as wheat substitution in biscuit formulation is able to increase fibre content in biscuit. The aims of this research were to determine the effect of Nypa fruticans flour to the physicochemical and sensory properties of high-fiber biscuit. This research used a completely randomized design (CRD) with the concentration of Nypa fruticans flour (0, 10, 20, 30, 40, 50, and 60%) as the treatments. Data was analysed by ANOVA and DnMRT at 95% confidence level. The result showed that Nypa flour had 10% water content , 3,18% crude fiber content and color characteristic L * = 87,57; a * = -3,33; and b * = 20,17. The concentration of Nypa flour significantly affect water and crude fiber content, color characteristic, crispyness and grit, but did not significantly affect hardness, spread ratio, color (sensory), taste, aroma, overall acceptance and multiple comparison. The concentration of 40% nypa flour was the best treatment to produce high-fiber biscuit with 2,78% water content, 1,47% crude fiber content, hardness 1301,3 gF, spread ratio 5,15, color characteristic (L * = 75,51; a * = 0,18; b * = 30,00), color description (brownish yellow), slightly crunchy, rough, taste (rather liked), aroma (rather liked), and overall acceptance (rather liked). Multiple comparison tests showed that the biscuit favored by panelists similar to the reference biscuit.